Gaya Kepemimpinan Dan Motivasi Pengaruhnya Terhadap Semangat Kerja Karyawan Hotel Siesta Legian - Wayan Arya Paramarta; Ni Made Ema Pradnya Kumala; Ni Ketut Laswitarni; Ni Made Gunastri (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2022)
This study aims to analyze the effect of leadership style and motivation on spirit of work at Hotel Siesta Legian. The research method used is multiple linear regression analysis method, this study uses primary data taken from distributing questionnaires to employees of Hotel Siesta Legian. The results of this study show that partially the leadership style and motivation have a positive influence on spirit of work, and simultaneously leadership style and motivation have a significant influence on spirit of work.